Low-frequency high-performance heat-conducting wave-absorbing material and preparation method thereof

CN122992336APending Publication Date: 2026-10-27CHERY AUTOMOBILE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611382860.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]然而,现有技术尚无同时满足该低频吸波与高导热双重要求的成熟方案

Benefits of technology

本发明提供的低频高性能导热吸波材料,通过铁镍合金吸收剂、导热填料、偶联剂、硅油和催化剂的协同配合,实现低频吸波与高导热性能。铁镍合金吸收剂为片状铁镍合金具有更高磁导率和耐腐蚀性,低频吸波性能显著提升;导热填料的引入有效提高材料整体导热系数;偶联剂改善吸收剂与填料在硅油基体中的分散性与界面结合,增强复合体系稳定性;乙烯基硅油与含氢硅油复配构成可交联硅基体,其中乙烯基硅油提供基础聚合物骨架与交联活性位点,含氢硅油作为交联剂参与固化,二者协同赋予材料良好的成型性、力学柔韧性与环境适应性;各原料共同作用,使材料在0.1-2 GHz频段具备良好吸波能力,同时显著提升导热性能,满足高功率电子器件对散热与电磁兼容的协同要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992336A_ABST
    Figure CN122992336A_ABST
Patent Text Reader

Abstract

The application provides a low-frequency high-performance heat-conducting wave-absorbing material and a preparation method thereof, relates to the technical field of heat-conducting wave-absorbing materials, and the main raw materials of the low-frequency high-performance heat-conducting wave-absorbing material include an iron-nickel alloy absorbent, a heat-conducting filler, a coupling agent, silicone oil and a catalyst; wherein the iron-nickel alloy absorbent is a flaky iron-nickel alloy. The low-frequency high-performance heat-conducting wave-absorbing material provided by the application has the combined action of various raw materials, so that the material has good wave-absorbing capacity in the 0.1-2 GHz frequency band, and the heat-conducting performance is significantly improved, thereby meeting the cooperative requirements of high-power electronic devices on heat dissipation and electromagnetic compatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermally conductive and microwave absorbing materials, and in particular to a low-frequency, high-performance thermally conductive and microwave absorbing material and its preparation method. Background Technology

[0002] Thermally conductive and electromagnetically absorbing materials possess both thermal conductivity and electromagnetic wave absorption capabilities, dissipating heat from devices and attenuating electromagnetic radiation. Currently, most commercially available products operate at frequencies above 2 GHz, with very few low-frequency materials available. Even those with low-frequency solutions generally have thermal conductivity <1 W / m·K, failing to meet heat dissipation requirements. New energy vehicle electronic control systems operate under high voltage, and power devices generate both heat and electromagnetic interference, affecting the stability of vehicle communication and accelerating component aging. Traditional discrete heat dissipation and shielding solutions are complex and space-consuming. Ideally, thermally conductive and electromagnetically absorbing materials should possess good absorption performance in the 0.1-2 GHz range and have a thermal conductivity ≥2 W / m·K.

[0003] However, there is currently no mature solution that simultaneously meets the dual requirements of low-frequency absorption and high thermal conductivity. CN119529776A uses vacuum melting to prepare the absorbent, which has high thermal conductivity and good aging resistance, but its main frequency band is >2 GHz; CN111031776A improves low-frequency performance by introducing a conductive flexible layer, but its main frequency is 3 GHz, and its reflection loss is only 3~ 5dB, performance is average.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] One of the objectives of this invention is to provide a low-frequency, high-performance thermally conductive and microwave-absorbing material to at least solve one of the technical problems existing in the prior art.

[0006] The second objective of this invention is to provide a method for preparing a low-frequency, high-performance thermally conductive and microwave-absorbing material.

[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a low-frequency high-performance thermally conductive and microwave-absorbing material, the main raw materials of which include: iron-nickel alloy absorber, thermally conductive filler, coupling agent, silicone oil and catalyst; The iron-nickel alloy absorbent is a sheet-like iron-nickel alloy, and the silicone oil includes vinyl silicone oil and hydrogen-containing silicone oil.

[0008] Furthermore, in the iron-nickel alloy absorbent, the iron content is 10% to 90%, and the remainder is nickel; Preferably, the thermally conductive filler comprises one or more of alumina, zinc oxide, boron nitride, and aluminum nitride; Preferably, the average particle size of the thermally conductive filler is 0.5 μm to 80 μm; Preferably, the coupling agent comprises one or more of vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, and hexadecyltriethoxysilane. Preferably, the vinyl content in the vinyl silicone oil is 0.5% to 5%; Preferably, the hydrogen content in the hydrogen-containing silicone oil is 0.05% to 1.5%; Preferably, the catalyst comprises a platinum catalyst.

[0009] Furthermore, by weight, the main raw materials of the low-frequency high-performance thermally conductive and microwave-absorbing material include: 350–850 parts iron-nickel alloy absorbent, 45–250 parts thermally conductive filler, 100 parts vinyl silicone oil, 0.5–25 parts hydrogen-containing silicone oil, 0.5–15 parts coupling agent, and 0.005–0.1 parts catalyst; More preferably, the main raw materials of the low-frequency high-performance thermally conductive and microwave-absorbing material, by weight, include: 400-800 parts of iron-nickel alloy absorbent, 50-200 parts of thermally conductive filler, 100 parts of vinyl silicone oil, 1-20 parts of hydrogen-containing silicone oil, 1-10 parts of coupling agent and 0.005-0.1 parts of catalyst.

[0010] Secondly, the present invention provides a method for preparing a low-frequency, high-performance thermally conductive and microwave-absorbing material, comprising: The iron-nickel alloy absorber, thermally conductive filler, coupling agent, silicone oil and catalyst are mixed and stirred under heating conditions to obtain the low-frequency high-performance thermally conductive and microwave absorbing material.

[0011] Furthermore, the mixing includes: (a) The iron-nickel alloy absorbent, thermally conductive filler, coupling agent and vinyl silicone oil are mixed and stirred under heating and vacuum conditions to obtain a first mixture; (b) Add hydrogen-containing silicone oil and catalyst to the first mixture and stir under a first temperature and vacuum conditions to obtain a second mixture; Preferably, in step (a), the heating temperature is 120℃~180℃, the vacuum degree is -0.05MPa~-0.1MPa, and the heating vacuum stirring time is 0.5h~6h; Preferably, in step (b), the first temperature is 5℃~25℃, the vacuum degree is -0.05MPa~-0.1MPa, and the stirring time is 0.5h~3h.

[0012] Furthermore, the iron-nickel alloy absorbent is prepared through the following steps: (A) Iron powder and nickel powder are mechanically alloyed to obtain an iron-nickel alloy; (B) The iron-nickel alloy is subjected to a sheet-like treatment; (C) Annealing the sheet-like iron-nickel alloy to obtain the iron-nickel alloy absorbent.

[0013] Furthermore, in step (A), the mechanical alloying is carried out using a planetary ball mill with a ball-to-material ratio of 10:1 to 40:1 and a milling time of 4 h to 40 h. Preferably, the average particle size of the iron powder and the nickel powder is independently 2 μm to 60 μm.

[0014] Furthermore, in step (B), the flake-forming process is performed using a vibratory ball mill with a ball-to-material ratio of 10:1 to 40:1 and a milling time of 4 h to 40 h.

[0015] Furthermore, in step (C), the annealing temperature is 150–650°C, preferably 200–600°C, and the time is 20 min–5 h, preferably 0.5 h–4 h.

[0016] Furthermore, the preparation method further includes: calendering the second mixture; Preferably, the thickness of the low-frequency high-performance thermally conductive and microwave-absorbing material obtained by calendering is 1.5 mm to 2.5 mm.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The low-frequency, high-performance thermally conductive microwave absorbing material provided by this invention achieves both low-frequency microwave absorption and high thermal conductivity through the synergistic combination of an iron-nickel alloy absorber, a thermally conductive filler, a coupling agent, silicone oil, and a catalyst. The iron-nickel alloy absorber, being a sheet-like iron-nickel alloy, possesses higher magnetic permeability and corrosion resistance, significantly improving low-frequency microwave absorption performance. The introduction of the thermally conductive filler effectively increases the overall thermal conductivity of the material. The coupling agent improves the dispersion and interfacial bonding of the absorber and filler in the silicone oil matrix, enhancing the stability of the composite system. Vinyl silicone oil and hydrogen-containing silicone oil are compounded to form a crosslinkable silicone matrix, where the vinyl silicone oil provides the basic polymer framework and crosslinking active sites, and the hydrogen-containing silicone oil participates in curing as a crosslinking agent. Together, they endow the material with good formability, mechanical flexibility, and environmental adaptability. The combined effect of all raw materials enables the material to possess good microwave absorption capabilities in the 0.1-2 GHz frequency band, while significantly improving thermal conductivity, meeting the synergistic requirements of high-power electronic devices for heat dissipation and electromagnetic compatibility. Attached Figure Description

[0018] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0019] Figure 1 This is a SEM image of the high-performance FeNi alloy absorbent prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the high-performance FeNi alloy absorbent prepared in Example 2 of the present invention; Figure 3 This is a SEM image of the high-performance FeNi alloy absorbent prepared in Example 3 of the present invention; Figure 4 This is a SEM image of the high-performance FeNi alloy absorbent prepared in Example 4 of the present invention. Detailed Implementation

[0020] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.

[0021] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] The first aspect of this invention provides a low-frequency, high-performance thermally conductive and microwave-absorbing material, the main raw materials of which include: an iron-nickel alloy absorber, a thermally conductive filler, a coupling agent, silicone oil, and a catalyst; wherein, the iron-nickel alloy absorber is a sheet-like iron-nickel alloy; and the silicone oil includes vinyl silicone oil and hydrogen-containing silicone oil.

[0023] In some preferred embodiments, the iron-nickel alloy absorbent is prepared by mechanical alloying, followed by flake formation and annealing.

[0024] The low-frequency, high-performance thermally conductive and microwave-absorbing material provided by this invention uses an iron-nickel alloy (FeNi alloy) as the absorbent. Compared with other absorbents, the iron-nickel alloy absorbent has higher magnetic permeability and is more resistant to corrosion and oxidation. After the iron-nickel alloy powder is flaked and annealed, the magnetic permeability is further improved, and the low-frequency performance is greatly enhanced. At the same time, it can also take into account the high-frequency microwave-absorbing performance. After the high-performance thermally conductive filler is combined in the thermally conductive and microwave-absorbing material, the thermal conductivity is significantly improved. While solving the electromagnetic interference problem, it can provide stable heat dissipation performance for related high-power devices, ensuring that the equipment is always in a stable working state.

[0025] Vinyl silicone oil provides crosslinkable active sites, while hydrogen-containing silicone oil acts as a crosslinking agent in the curing process. The combined use of these two materials helps to achieve uniform curing and good molding of the material.

[0026] In some preferred embodiments, based on the total mass of the iron-nickel alloy absorbent as 100%, the iron content is 10% to 90%, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, etc., and the remainder is nickel.

[0027] In some preferred embodiments, the thermally conductive filler includes one or more of alumina, zinc oxide, boron nitride, and aluminum nitride. The average particle size of the thermally conductive filler is 0.5 μm to 80 μm, for example, it can be 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, 80 μm, etc.

[0028] In this invention, the average particle size range of the above-mentioned thermally conductive filler takes into account both dispersibility and the construction of thermally conductive pathways: if it is too fine (<0.5 μm), it is easy to agglomerate and reduce effective filling, while if it is too large (>80 μm), it will affect the interfacial bonding and material flexibility.

[0029] In some preferred embodiments, the coupling agent comprises one or more of vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, and hexadecyltriethoxysilane. In this invention, the coupling agent can improve the dispersibility and interfacial bonding strength of the absorbent and thermally conductive filler in the silicone oil matrix.

[0030] In some preferred embodiments, the vinyl content in the vinyl silicone oil is 0.5% to 5%, for example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, etc.

[0031] In some preferred embodiments, the hydrogen content in the hydrogen-containing silicone oil is 0.05% to 1.5%, for example, it can be 0.05%, 0.1%, 0.5%, 1.0%, 1.5%, etc.

[0032] In some preferred embodiments, the catalyst comprises a platinum catalyst.

[0033] In some preferred embodiments, the main raw materials of the low-frequency high-performance thermally conductive and microwave-absorbing material, by weight, include: 350 to 850 parts of iron-nickel alloy absorbent, for example, 350 parts, 400 parts, 450 parts, 500 parts, 550 parts, 600 parts, 650 parts, 700 parts, 750 parts, 800 parts, 850 parts, etc., more preferably 400 to 800 parts; 45 to 250 parts of thermally conductive filler, for example, 45 parts, 50 parts, 100 parts, 150 parts, 200 parts, 250 parts, etc., more preferably 50 to 200 parts; 100 parts vinyl silicone oil; 0.5 to 25 parts of hydrogen-containing silicone oil, for example, 0.5 parts, 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, etc., more preferably 1 to 20 parts; 0.5 to 15 parts of coupling agent, for example, 0.5 parts, 1 part, 5 parts, 10 parts, 15 parts, etc., more preferably 1 to 10 parts; 0.005 to 0.1 parts of catalyst, for example, 0.005 parts, 0.01 parts, 0.1 parts, etc.

[0034] A second aspect of this invention provides a method for preparing a low-frequency, high-performance thermally conductive and microwave-absorbing material, comprising: The iron-nickel alloy absorber, thermally conductive filler, coupling agent, silicone oil and catalyst are mixed and stirred under heating conditions to obtain the low-frequency high-performance thermally conductive and microwave absorbing material.

[0035] The iron-nickel alloy absorbent is prepared through the following steps: (A) Iron powder and nickel powder are mechanically alloyed to obtain an iron-nickel alloy; (B) The iron-nickel alloy is subjected to a sheet-like treatment; (C) Annealing the sheet-like iron-nickel alloy to obtain the iron-nickel alloy absorbent.

[0036] The FeNi absorbent prepared by this three-step method achieves composition homogenization through mechanical alloying, enhances magnetic anisotropy and low-frequency response through lamellarization, and optimizes the crystal phase structure and improves magnetic permeability and stability through annealing.

[0037] In some preferred embodiments, in step (A), the mechanical alloying is carried out using a planetary ball mill with a ball-to-material ratio of 10:1 to 40:1, such as 10:1, 20:1, 30:1, 40:1, etc., and the ball milling time is 4 h to 40 h, such as 4 h, 10 h, 20 h, 30 h, 40 h, etc.

[0038] Preferably, the average particle size of the iron powder and the nickel powder is independently between 2 μm and 60 μm, for example, 2 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, etc. This particle size range takes into account both reactivity and dispersion stability: if it is too fine, it is easy to oxidize and agglomerate; if it is too large, alloying will be insufficient.

[0039] In some preferred embodiments, in step (B), the sheet-forming process is performed using a vibratory ball mill, the ball milling medium is anhydrous ethanol, the ball-to-material ratio is 10:1 to 40:1, for example, 10:1, 20:1, 30:1, 40:1, etc., and the ball milling time is 4h to 40h, for example, 4h, 10h, 20h, 30h, 40h, etc.

[0040] In some preferred embodiments, in step (C), the annealing temperature is 150–650°C, preferably 200–600°C, for example, 200°C, 400°C, 600°C, etc., and the time is 20 min–5 h, preferably 0.5 h–4 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, etc., and the annealing atmosphere is an argon-hydrogen mixture.

[0041] In some preferred embodiments, the mixing includes: (a) The iron-nickel alloy absorbent, thermally conductive filler, coupling agent and vinyl silicone oil are mixed and stirred under high temperature heating and vacuum conditions to obtain a first mixture; the heating temperature is 120℃~180℃, for example, 120℃, 140℃, 160℃, 180℃, etc., the vacuum degree is -0.05MPa~-0.1MPa, and the heating vacuum stirring time is 0.5h~6h, for example, 0.5h, 1h, 3h, 6h, etc. (b) Add hydrogen-containing silicone oil and catalyst to the first mixture and stir under low temperature (i.e., the first temperature) and vacuum conditions to obtain a second mixture; the low temperature is 5℃ to 25℃, for example, 5℃, 10℃, 15℃, 20℃, 25℃, etc., the vacuum degree is -0.05MPa to -0.1MPa, and the stirring time is 0.5h to 3h, for example, 0.5h, 1h, 2h, 3h, etc.

[0042] This invention employs a stepwise mixing process. First, the absorbent, thermally conductive filler, coupling agent, and vinyl silicone oil are premixed at high temperature to form a stable premix. Then, hydrogen-containing silicone oil and a catalyst are introduced at low temperature. This avoids the catalyst causing crosslinking of the premix at high temperature and ensures thorough mixing of Si-H and vinyl groups, thereby obtaining a highly uniform composite material. Simultaneously, stepwise temperature-controlled vacuum stirring facilitates phased processing: the high-temperature stage promotes the hydrolysis and condensation of the coupling agent and the dispersion of the filler, while the low-temperature stage inhibits premature hydrosilylation, ensuring mixing uniformity and process controllability.

[0043] In some preferred embodiments, the preparation method further includes: calendering the second mixture; preferably, the thickness of the low-frequency high-performance thermally conductive and microwave-absorbing material obtained by calendering is 1.5 mm-2.5 mm. Calendering is a mature process with high dimensional accuracy, which is beneficial for obtaining flexible sheets with uniform thickness and smooth surface; a thickness of 1.5-2.5 mm is preferred, balancing low-frequency microwave absorption performance and assembly compatibility.

[0044] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.

[0045] Example 1 This embodiment provides a low-frequency, high-performance thermally conductive and microwave-absorbing material, the preparation process of which is as follows: (1) Preparation of FeNi alloy absorbent: Fe (average particle size 30 μm) and Ni powder (average particle size 30 μm) were prepared by using a planetary ball mill at a mass ratio of 50:50 to form Fe. 50 Ni 50 The alloy, with a ball-to-material ratio of 20:1, was ball-milled for 20 hours; a vibratory ball mill was used to process Fe. 50 Ni 50 The alloy was subjected to a flake-forming treatment with a ball-to-material ratio of 20:1 and a ball milling time of 20 h. The ball milling medium was anhydrous ethanol. The prepared flake-shaped absorbent was annealed at 500 °C for 4 h in an argon-hydrogen mixed atmosphere to obtain a high-performance FeNi alloy absorbent.

[0046] (2) Preparation of the first mixture: 600g of the prepared high-performance FeNi alloy absorbent, 150g of alumina thermally conductive powder (average particle size of 40μm), 10g of coupling agent hexadecyltriethoxysilane, and 100g of vinyl silicone oil (Runhe RH-Vi100E, vinyl content 1%) were mixed evenly using a mixer and then stirred under high temperature and vacuum to obtain the first mixture. The heating and vacuum stirring time was 4h, the temperature was 150℃, and the vacuum degree was -0.09MPa.

[0047] (3) Preparation of the second mixture: 10g of hydrogen-containing silicone oil (0.55% hydrogen content of Runhe RH-H503) and 0.05g of platinum catalyst were added to the first mixture and stirred under low temperature vacuum to obtain the second mixture; the low temperature vacuum stirring time was 1h, the temperature was 15℃, and the vacuum degree was -0.09MPa.

[0048] (4) Finally, the mixed rubber compound is prepared into a 2mm thick thermally conductive and microwave-absorbing material by calendering.

[0049] Example 2 This embodiment provides a low-frequency, high-performance thermally conductive and microwave-absorbing material, the preparation process of which is as follows: (1) Preparation of FeNi alloy absorbent: Fe (average particle size 30 μm) and Ni powder (average particle size 30 μm) were prepared by using a planetary ball mill at a mass ratio of 90:10 to form Fe... 90 Ni 10 The alloy, with a ball-to-material ratio of 40:1, was ball-milled for 10 hours; a vibratory ball mill was used to process Fe. 90 Ni 10 The alloy was subjected to a flake-forming treatment with a ball-to-material ratio of 40:1 and a ball milling time of 10 h. The ball milling medium was anhydrous ethanol. The prepared flake-shaped absorbent was annealed at 400 °C for 4 h in an argon-hydrogen mixed atmosphere to obtain a high-performance FeNi alloy absorbent. (2) Preparation of the first mixture: 800g of the prepared high-performance FeNi alloy absorbent, 50g of zinc oxide thermal conductive powder (average particle size of 40μm), 8g of coupling agent hexadecyltriethoxysilane, and 100g of vinyl silicone oil (Runhe RH-Vi100E, vinyl content 1%) were mixed evenly using a mixer and stirred under high temperature and vacuum to obtain the first mixture. The heating and vacuum stirring time was 3h, the temperature was 150℃, and the vacuum degree was -0.09MPa.

[0050] (3) Preparation of the second mixture: 10g of hydrogen-containing silicone oil (Runhe RH-H503 hydrogen content 0.55%) and 0.05g of platinum catalyst were added to the first mixture and stirred under low temperature vacuum to obtain the second mixture; the low temperature vacuum stirring time was 0.5h, the temperature was 20℃, and the vacuum degree was -0.09MPa.

[0051] (4) Finally, the mixed rubber compound is prepared into a 2mm thick thermally conductive and microwave-absorbing material by calendering.

[0052] Example 3 This embodiment provides a low-frequency, high-performance thermally conductive and microwave-absorbing material, the preparation process of which is as follows: (1) Preparation of FeNi alloy absorbent: Fe (average particle size 30 μm) and Ni powder (average particle size 30 μm) were prepared by using a planetary ball mill at a mass ratio of 10:90 to form Fe... 10 Ni 90 The alloy, with a ball-to-material ratio of 20:1, was ball-milled for 20 hours; a vibratory ball mill was used to process Fe. 10 Ni 90 The alloy was subjected to a flake-forming treatment with a ball-to-material ratio of 20:1 and a ball milling time of 20 h. The ball milling medium was anhydrous ethanol. The prepared flake-shaped absorbent was annealed at 500 °C for 2 h in an argon-hydrogen mixed atmosphere to obtain a high-performance FeNi alloy absorbent.

[0053] (2) Preparation of the first mixture: The prepared high-performance Fe 10 Ni 90 400g of alloy absorbent, 200g of aluminum nitride thermally conductive powder (average particle size 40μm), 8g of coupling agent hexadecyltriethoxysilane, and 100g of vinyl silicone oil (Runhe RH-Vi100E, vinyl content 1%) were mixed evenly using a mixer and then subjected to high-temperature vacuum stirring to obtain the first mixture. The heating and vacuum stirring time was 4h, the temperature was 150℃, and the vacuum degree was -0.09MPa.

[0054] (3) Preparation of the second mixture: 10g of hydrogen-containing silicone oil (0.55% hydrogen content of Runhe RH-H503) and 0.05g of platinum catalyst were added to the first mixture and stirred under low temperature vacuum to obtain the second mixture; the low temperature vacuum stirring time was 1h, the temperature was 10℃, and the vacuum degree was -0.09MPa.

[0055] (4) Finally, the mixed rubber compound is prepared into a 2mm thick thermally conductive and microwave-absorbing material by calendering.

[0056] Example 4 This embodiment provides a low-frequency, high-performance thermally conductive and microwave-absorbing material, the preparation process of which is as follows: (1) Preparation of FeNi alloy absorbent: Fe (average particle size 30 μm) and Ni powder (average particle size 30 μm) were prepared by using a planetary ball mill at a mass ratio of 70:30 to form Fe. 70 Ni 30 The alloy, with a ball-to-material ratio of 40:1, was ball-milled for 10 hours; a vibratory ball mill was used to process Fe. 70 Ni 30 The alloy was subjected to a flake-forming treatment with a ball-to-material ratio of 30:1 and a ball milling time of 20 h. The ball milling medium was anhydrous ethanol. The prepared flake-shaped absorbent was annealed at 500 °C for 3 h in an argon-hydrogen mixed atmosphere to obtain a high-performance FeNi alloy absorbent.

[0057] (2) Preparation of the first mixture: 600g of the prepared high-performance FeNi alloy absorbent, 150g of boron nitride thermal conductive powder (average particle size of 40μm), 10g of coupling agent hexadecyltriethoxysilane, and 100g of vinyl silicone oil (Runhe RH-Vi100E, vinyl content 1%) were mixed evenly using a mixer and then stirred under high temperature and vacuum to obtain the first mixture. The heating and vacuum stirring time was 2h, the temperature was 160℃, and the vacuum degree was -0.09MPa.

[0058] (3) Preparation of the second mixture: 10g of hydrogen-containing silicone oil (0.55% hydrogen content of Runhe RH-H503) and 0.05g of platinum catalyst were added to the first mixture and stirred under low temperature vacuum to obtain the second mixture; the low temperature vacuum stirring time was 1h, the temperature was 20℃, and the vacuum degree was -0.09MPa.

[0059] (4) Finally, the mixed rubber compound is prepared into a 2mm thick thermally conductive and microwave-absorbing material by calendering.

[0060] Example 5 This embodiment provides a low-frequency, high-performance thermally conductive and microwave-absorbing material, which differs from Embodiment 1 in that: In step (1), the annealing temperature is adjusted to 200℃ and the time is adjusted to 4h; In step (2), the coupling agent is adjusted to 1g; the heating and vacuum stirring time is adjusted to 0.5h, and the temperature is 180℃. In step (3), the amount of hydrogen-containing silicone oil is adjusted to 1g and the amount of platinum catalyst is adjusted to 0.005g; the low-temperature vacuum stirring time is adjusted to 3h and the temperature is 5℃.

[0061] Example 6 This embodiment provides a low-frequency, high-performance thermally conductive and microwave-absorbing material, which differs from Embodiment 1 in that: In step (1), the annealing temperature is adjusted to 600℃ and the time is adjusted to 0.5h; In step (2), the heating and vacuum stirring time is adjusted to 6 hours and the temperature is 120°C; In step (3), the amount of hydrogen-containing silicone oil is adjusted to 20g and the amount of platinum catalyst is adjusted to 1g; the low-temperature vacuum stirring time is adjusted to 0.5h and the temperature is 25℃.

[0062] Example 7 This embodiment provides a low-frequency, high-performance thermally conductive and microwave-absorbing material, which differs from Embodiment 1 in that: In step (2), the FeNi alloy absorbent is adjusted to 850g, the alumina thermally conductive filler is adjusted to 45g, and the coupling agent is adjusted to 15g; In step (3), the amount of hydrogen-containing silicone oil is adjusted to 0.5g.

[0063] Example 8 This embodiment provides a low-frequency, high-performance thermally conductive and microwave-absorbing material, which differs from Embodiment 1 in that: In step (2), the FeNi alloy absorbent is adjusted to 350g, the alumina thermally conductive filler is adjusted to 250g, and the coupling agent is adjusted to 0.5g; In step (3), the amount of hydrogen-containing silicone oil is adjusted to 25g.

[0064] Example 9 This embodiment provides a low-frequency high-performance thermally conductive and microwave-absorbing material. The difference from Embodiment 1 is that in step (1), the annealing temperature is adjusted to 150°C and the time is adjusted to 5 h.

[0065] Example 10 This embodiment provides a low-frequency, high-performance thermally conductive and microwave-absorbing material. The difference from Embodiment 1 is that in step (1), the annealing temperature is adjusted to 650°C and the time is adjusted to 20 minutes.

[0066] Example 11 This embodiment provides a thermally conductive and microwave-absorbing material, which differs from Embodiment 1 in that the sheet-forming process is omitted.

[0067] Comparative Example 1 This comparative example provides a thermally conductive and microwave-absorbing material, which differs from Example 1 in that: in step (2), no thermally conductive filler is added, and the FeNi alloy absorber is adjusted to 850g.

[0068] Comparative Example 2 This comparative example provides a thermally conductive and microwave-absorbing material, which differs from Example 1 in that it does not contain hydrogen-containing silicone oil.

[0069] Comparative Example 3 This comparative example provides a thermally conductive and microwave-absorbing material, which differs from Example 1 in that the absorber uses commonly available commercially available sheet-like Fe. 85 Si 9.6 Al 5.4 Absorbent.

[0070] The performance of the absorbing materials in the examples and comparative examples was tested as follows: Thermal conductivity test. The test was conducted according to standard ASTM D5470, using a 30mm diameter disc as the sample.

[0071] Magnetic permeability testing. The cured microwave absorbing sheet was stamped into a coaxial ring with an inner diameter of 3.04 mm and an outer diameter of 7 mm, and then the magnetic permeability at 1 GHz was measured using a vector network analyzer.

[0072] Reflectivity test. The test was conducted in accordance with standard GJB2038A, with a sample size of 500mm × 500mm.

[0073] Double 85 aging test. The test was conducted in accordance with standard GB / T2423.50, and the test duration was 1000 hours.

[0074] The test results are shown in Table 1.

[0075] Table 1

[0076] As can be seen from the data in Table 1, the overall performance of each embodiment is better than that of the comparative example. The data of Examples 1-4 show that when the iron content of the iron-nickel alloy absorbent is in the range of 10% to 90% and the amount of thermally conductive filler is in the preferred range, the material achieves a good balance between low-frequency wave absorption performance and thermal conductivity performance. Among them, the overall performance of Examples 1 and 4 is particularly balanced.

[0077] The data from Examples 1, 5-6, and 7-8 show that when the process parameters and raw material dosage are within the preferred range, the thermal conductivity and reflection loss of the material remain at a good level, indicating that the range of process parameters can effectively ensure the optimization of the magnetic properties of the absorbent and the uniform curing of the matrix.

[0078] Data from Examples 1 and 9-10 show that when the annealing temperature is below 200℃, the absorber crystal phase optimization is insufficient, the magnetic permeability decreases, and the reflection loss decreases accordingly; when the annealing temperature is above 600℃, the absorption performance also decreases to some extent.

[0079] The data from Examples 1 and 11 show that the thermal conductivity of the material is improved after the sheeting treatment is removed, but the reflection loss is significantly reduced, indicating that the sheeting treatment plays an indispensable role in achieving low-frequency high-efficiency wave absorption.

[0080] The data from Example 1 and Comparative Example 1 show that the thermal conductivity of the material decreases significantly when no thermally conductive filler is added, demonstrating the key role of the thermally conductive filler in constructing the thermal conduction path.

[0081] In Comparative Example 2, no hydrogen-containing silicone oil was added, resulting in the lack of silane-hydrogen bonds (Si-H) required for cross-linking in the system. The hydrosilylation reaction could not occur, and the vinyl silicone oil could not form a three-dimensional cross-linked network. The material remained in a paste state and could not be cured and molded, so no effective test sample could be obtained.

[0082] As can be seen from the data in Example 1 and Comparative Example 3, using commercially available Fe... 85 Si 9.6 Al 5.4When using absorbents, the thermal conductivity and reflection loss of the material are not as good as those of the embodiment using FeNi alloy absorbents, and the performance degradation after double 85 aging is more obvious, further demonstrating the dual advantages of the FeNi alloy absorbent of the present invention in terms of low-frequency wave absorption performance and aging resistance.

[0083] pass Figure 1-4 It can be seen that the difference in the mass ratio of Fe and Ni leads to significant differences in the morphology after ball milling. Ni material itself is relatively soft and easily forms flakes, so the Fe in Example 3... 10 Ni 90 The Ni content is high, and the flaky particles after ball milling are larger and have the highest aspect ratio. Example 1 is second, and the degree of flaky formation in Example 2 is better than that in Example 4. This is because the ball milling time in Example 4 is longer, and the flaky particles begin to break and weld, resulting in a smaller overall particle size and a thicker longitudinal direction.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low-frequency, high-performance thermally conductive and microwave-absorbing material, characterized in that, Its main raw materials include: iron-nickel alloy absorbent, thermally conductive filler, coupling agent, silicone oil and catalyst; The iron-nickel alloy absorbent is a sheet-like iron-nickel alloy, and the silicone oil includes vinyl silicone oil and hydrogen-containing silicone oil.

2. The low-frequency high-performance thermally conductive and microwave-absorbing material according to claim 1, characterized in that, The iron-nickel alloy absorbent contains 10% to 90% iron, with the remainder being nickel; Preferably, the thermally conductive filler comprises one or more of alumina, zinc oxide, boron nitride, and aluminum nitride; Preferably, the average particle size of the thermally conductive filler is 0.5 μm to 80 μm; Preferably, the coupling agent comprises one or more of vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, and hexadecyltriethoxysilane. Preferably, the vinyl content in the vinyl silicone oil is 0.5% to 5%; Preferably, the hydrogen content in the hydrogen-containing silicone oil is 0.05% to 1.5%; Preferably, the catalyst comprises a platinum catalyst.

3. The low-frequency high-performance thermally conductive and microwave-absorbing material according to claim 1, characterized in that, The main raw materials of the low-frequency high-performance thermally conductive and microwave-absorbing material, by weight, include: 350–850 parts iron-nickel alloy absorbent, 45–250 parts thermally conductive filler, 100 parts vinyl silicone oil, 0.5–25 parts hydrogen-containing silicone oil, 0.5–15 parts coupling agent, and 0.005–0.1 parts catalyst; More preferably, the main raw materials of the low-frequency high-performance thermally conductive and microwave-absorbing material, by weight, include: 400-800 parts of iron-nickel alloy absorbent, 50-200 parts of thermally conductive filler, 100 parts of vinyl silicone oil, 1-20 parts of hydrogen-containing silicone oil, 1-10 parts of coupling agent and 0.005-0.1 parts of catalyst.

4. The method for preparing the low-frequency high-performance thermally conductive and microwave-absorbing material according to any one of claims 1-3, characterized in that, include: The iron-nickel alloy absorber, thermally conductive filler, coupling agent, silicone oil and catalyst are mixed and stirred under heating conditions to obtain the low-frequency high-performance thermally conductive and microwave absorbing material.

5. The method for preparing low-frequency high-performance thermally conductive and microwave-absorbing material according to claim 4, characterized in that, The mixture includes: (a) The iron-nickel alloy absorbent, thermally conductive filler, coupling agent and vinyl silicone oil are mixed and stirred under heating and vacuum conditions to obtain a first mixture; (b) Add hydrogen-containing silicone oil and catalyst to the first mixture and stir under a first temperature and vacuum conditions to obtain a second mixture; Preferably, in step (a), the heating temperature is 120℃~180℃, the vacuum degree is -0.05MPa~-0.1MPa, and the heating vacuum stirring time is 0.5h~6h; Preferably, in step (b), the first temperature is 5℃~25℃, the vacuum degree is -0.05MPa~-0.1MPa, and the stirring time is 0.5h~3h.

6. The method for preparing low-frequency high-performance thermally conductive and microwave-absorbing material according to claim 4, characterized in that, The iron-nickel alloy absorbent is prepared by the following steps: (A) Iron powder and nickel powder are mechanically alloyed to obtain an iron-nickel alloy; (B) The iron-nickel alloy is subjected to a sheet-like treatment; (C) Annealing the sheet-like iron-nickel alloy to obtain the iron-nickel alloy absorbent.

7. The method for preparing the low-frequency high-performance thermally conductive and microwave-absorbing material according to claim 6, characterized in that, In step (A), the mechanical alloying is carried out using a planetary ball mill with a ball-to-material ratio of 10:1 to 40:1 and a milling time of 4 h to 40 h. Preferably, the average particle size of the iron powder and the nickel powder is independently 2 μm to 60 μm.

8. The method for preparing the low-frequency high-performance thermally conductive and microwave-absorbing material according to claim 6, characterized in that, In step (B), the flake-forming process is performed using a vibratory ball mill with a ball-to-material ratio of 10:1 to 40:1 and a milling time of 4 h to 40 h.

9. The method for preparing the low-frequency high-performance thermally conductive and microwave-absorbing material according to claim 6, characterized in that, In step (C), the annealing temperature is 150–650°C, preferably 200–600°C, and the time is 20 min–5 h, preferably 0.5 h–4 h.

10. The method for preparing low-frequency high-performance thermally conductive and microwave-absorbing material according to claim 5, characterized in that, The preparation method further includes: calendering the second mixture; Preferably, the thickness of the low-frequency high-performance thermally conductive and microwave-absorbing material obtained by calendering is 1.5 mm to 2.5 mm.

Citation Information

Patent Citations

  • Heat-conducting wave-absorbing gasket

    CN111031776A

  • High-reliability high-thermal-conductivity wave-absorbing material and preparation method thereof

    CN119529776A